High-intensity training elicits greater improvements in cardio-metabolic and reproductive outcomes than moderate-intensity training in women with polycystic ovary syndrome: a randomized clinical trial. Issue 5 (23rd March 2022) - Patten, Rhiannon K; McIlvenna, Luke C; Levinger, Itamar; Garnham, Andrew P; Shorakae, Soulmaz; Parker, Alexandra G; McAinch, Andrew J; Rodgers, Raymond J; Hiam, Danielle; Moreno-Asso, Alba; Stepto, Nigel K
Abstract: STUDY QUESTION: Does 12 weeks of high-intensity interval training (HIIT) result in greater improvements in cardio-metabolic and reproductive outcomes compared to standard moderate-intensity continuous training (MICT) in women with polycystic ovary syndrome (PCOS)? SUMMARY ANSWER: HIIT offers greater improvements in aerobic capacity, insulin sensitivity and menstrual cyclicity, and larger reductions in hyperandrogenism compared to MICT. WHAT IS KNOWN ALREADY: Exercise training is recognized to improve clinical outcomes in women with PCOS, but little is known about whether HIIT results in greater health outcomes compared to standard MICT. STUDY DESIGN, SIZE, DURATION: This was a two-armed randomized clinical trial enrolling a total of 29 overweight women with PCOS between May 2016 and November 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women with PCOS aged 18–45 years were randomly assigned to 12 weeks of either MICT (60–75% peak heart rate, N = 14) or HIIT (>90% peak heart rate, N = 15), each completed three times per week. The primary clinical outcomes were aerobic capacity (VO2peak ) and insulin sensitivity (euglycaemic–hyperinsulinaemic clamp). Secondary outcomes included hormonal profiles, menstrual cyclicity and body composition. MAIN RESULTS AND THE ROLE OF CHANCE: Both HIIT and MICT improved VO2peak (HIIT; Δ 5.8 ± 2.6 ml/kg/min, P < 0.001 and MICT; Δ 3.2 ± 2 ml/kg/min, P < 0.001), however, the HIIT group had a greater improvement in aerobic capacity compared to MICT ( β = 2.73 ml/kg/min, P = 0.015). HIIT increased the insulin sensitivity index compared to baseline (Δ 2.3 ± 4.4 AU, P = 0.007) and MICT ( β = 0.36 AU, P = 0.030), and caused higher increases in sex hormone-binding globulin compared to MICT ( β = 0.25 nmol/l, P = 0.002). HIIT participants were 7.8 times more likely to report improved menstrual cyclicity than those in the MICT group (odds ratio 7.8, P = 0.04). LIMITATIONS, REASONS FOR CAUTION: This study has a small sample size and the findings of the effect of the exercise interventions are limited to overweight reproductive-aged women, who do not have any co-existing co-morbidities that require medication. WIDER IMPLICATIONS OF THE FINDINGS: Exercise, regardless of intensity, has clear health benefits for women with PCOS. HIIT appears to be a more beneficial strategy and should be considered for promoting health and reducing cardio-metabolic risk in overweight women with PCOS. STUDY FUNDING/COMPETING INTEREST(s): This work was supported by a Project Support Grant from the Australian National Health and Medical Research Council (NHMRC) Centre for Research Excellence in PCOS. The authors have no conflicts of interest to disclose. TRIAL REGISTRATION NUMBER: ACTRN12615000242527. TRIAL REGISTRATION DATE: 19 February 2015. DATE OF FIRST PATIENT'S ENROLMENT: 27 May 2016.